2007
DOI: 10.1086/519848
|View full text |Cite
|
Sign up to set email alerts
|

Increased Rates of Preterm Delivery Are Associated with the Initiation of Highly Active Antiretrovial Therapy during Pregnancy: A Single‐Center Cohort Study

Abstract: It remains controversial whether in human immunodeficiency virus (HIV)-positive pregnant women an increased rate of preterm delivery is associated with highly active antiretroviral therapy (HAART). Since 1995 the management and outcome of all HIV-infected pregnant women delivering at St. Mary's Hospital London have been prospectively documented. The prevalence of preterm delivery and the correlation between gestational age and type of antiretroviral therapy were sought: preterm delivery occurred in 14.2% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
43
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 10 publications
4
43
1
Order By: Relevance
“…After review of the title and abstract, 187 full-text articles were selected for reading, and 11 studies met inclusion criteria (fi gure 1). 9,10,16,[21][22][23][24][25][26][27][28] The studies included participants recruited during the period 1986-2012 (table 1). Three were done in the UK, 10,23,26 two in Botswana, 9,28 and one each in Brazil, 24 France, 27 South Africa, 25 and Tanzania; 16 the remaining two studies 21,22 included participants from the European Collaborative Study (ECS).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After review of the title and abstract, 187 full-text articles were selected for reading, and 11 studies met inclusion criteria (fi gure 1). 9,10,16,[21][22][23][24][25][26][27][28] The studies included participants recruited during the period 1986-2012 (table 1). Three were done in the UK, 10,23,26 two in Botswana, 9,28 and one each in Brazil, 24 France, 27 South Africa, 25 and Tanzania; 16 the remaining two studies 21,22 included participants from the European Collaborative Study (ECS).…”
Section: Resultsmentioning
confidence: 99%
“…Prematurity was reported in ten studies. 9,10,16,21,[23][24][25][26][27][28] ART initiation before conception was associated with signifi cantly higher risk of prematurity than ART initiation after conception (pooled RR 1·20, 95% CI 1·01-1·44; fi gure 2). Between-study heterogeneity was signifi cant (I²=77%, 95% CI 57·3-87·4; p=0·0001), suggesting that about three-quarters of the variability in the measures of the association is due to heterogeneity between studies rather than chance (fi gure 2).…”
Section: Resultsmentioning
confidence: 99%
“…In the multivariate model after controlling for the effect of HIV related, obstetric, and demographic factors, women who received HAART were 3.4 times more likely [RR 3.350, 95% CI 1.520-7.383] to experience PB and 1.9 times more likely [RR 1.949, 95% CI 1.099-3.454] to experience APO in comparison to women who received AZT. Younger women (age [16][17][18][19][20] were also 3.4 times more likely [RR 3.370, 95% CI 1.031-11.012] to experience preterm birth in comparison to the older women (age > = 31).…”
Section: Resultsmentioning
confidence: 99%
“…While there is an increasing number of studies that suggest higher risk of preterm birth (PB) (< 37 weeks) [1][2][3][4][5][6][7] and low birth weight (LBW) 2,[8][9][10] among babies of women receiving HAART during pregnancy, there are also some studies that did not observe this association. [11][12][13][14][15][16] Most of the studies are from developed regions 4,[17][18][19] and only recently research findings are emerging from developing regions. 7,[20][21][22] Previous research from developed regions assessed the role of HAART containing protease inhibitors (PI), whereas the recent studies from developing regions have also evaluated the effect of PI excluded HAART on pregnancy outcomes (Table 1).…”
mentioning
confidence: 99%
“…Several studies from Europe have suggested that the initiation of ART during pregnancy may be associated with an increased risk of preterm delivery, particularly with protease inhibitor (PI)-containing regimens. [6][7][8] However, these findings have been contradicted by studies from Brazil and North America showing no association between maternal ART use and pregnancy outcomes. [9][10][11][12] In Africa, there have been some studies that evaluated the impact of ART on pregnancy outcomes.…”
mentioning
confidence: 99%